Financial Reporting Quality Among Deposit Taking Saccos: What Unties the Ties - Jonathan Muendo Kinyenze; Ibrahim Tirimba Ondabu (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
taking Saccos in Kenya by determining whether staff capacity, top management expertise, enterprise resource planning and the quality of internal audit unties the ties of the quality of financial reports. Through descriptive design and primary data of the one hundred and twenty-six respondents of the forty-two deposit taking Saccos (DT Saccos) in Kenya, the establishes that top management expertise, enterprise resource planning (ERP) and quality of internal audit had a strong positive significant influence on the quality of financial reporting while staff capacity had also a positive influence but which was weak in terms of the strength